Measurement of the production cross section for single top quarks in association with W bosons in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2018)
A measurement is presented of the associated production of a single top quark and a W boson in proton -proton collisions at root s = 13 TeV by the CMS Collaboration at the CERN LHC. The data collected corresponds to an integrated luminosity of 35.9 fb(-1). The measurement is performed using events with one electron and one muon in the final state along with at least one jet originated from a bottom quark. A multivariate discriminant, exploiting the kinematic properties of the events, is used to separate the signal from the dominant tt background. The measured cross section of 63.1 +/- 1.8(stat) +/- 6.4(syst) +/- 2.1 (lumi) pb is in agreement with the standard model expectation.
Keywords: Hadron-Hadron scattering (experiments); Top physics